DESENVOLVIMENTO, CARACTERIZAÇÃO E AVALIAÇÃO IN VIVO DE SISTEMAS DE LIBERAÇÃO MICROPARTICULADOS CONTENDO EFAVIRENZ - (:unkn) unknown (UNIVERSIDADE ESTADUAL DE PONTA GROSSA, 2016)
The efavirenz is the first choice drug of non-nucleoside reverse transcriptase inhibitors used in the treatment of HIV-1 infections. It belongs to class II of the Biopharmaceutics Classification System and your therapeutic dose is of 600 mg, taken before bedtime due the side effects. With the aim of improve the drug’s bioavailability with possible reduction of side effects, microparticles with Eudragit® L100 or S100 were developed by spray drying. The formulations M1 to M4 were prepared in ethanol:water (50:50, V/V) and M5 to M8 in ethanol:phosphate buffer pH 7.4 (50:50, V/V). Microparticles were obtained with yield (40 - 70%), humidity (1.41 - 5.77%), particle size (2.02 - 4.07 μm) and zeta potential (-61 to -43) suitable. The drug’s quantification was realized by high performance liquid chromatography analytical method developed and validated. The method proved to be specific, linear (r = 0.9997, n = 3), precise, accurate and robust in a range of 8.0 to 50.0 μg.mL-1, with analysis and retention time of 5.0 and 3.5 minutes, respectively. M1 to M4 showed spherical morphology with drug content between 90 - 104%, and M5 to M8 exhibited flattened and distorted morphology with drug content between 67 - 75%. No chemical interactions was observed in the Fourier transformed infrared spectrum for microparticles M1 to M4. However, there enlargement and increased intensity of some bands in the spectra of microparticles M5 to M8, suggesting a modification of chemical bonds. The thermal analysis and X ray diffraction indicated that the incorporation of EFV into the microparticles contributed to the amorphization of the drug. In vitro drug release confirmed the low solubility of the drug in water (22.88%). The microparticles released less than 22% in acid medium promoting higher release at pH 6.8. All formulations evaluated increased the drug solubility and dissolution efficiency, and exhibited biexponential release kinetics according to the applied mathematical models, being interesting strategies to increase the drug’s bioavailability. The M3 accounted for the major release in pH 6.8 (73.69%) and, according to the Korsmeyer-Peppas model showed anomalous transport characteristics (diffusion and erosion of the polymer), while in other microparticles the release process was controlled by diffusion. In in vitro assay the animals subjected to the administration of M3 exhibited less alterations in the biochemical parameters compared to treatment group EFV, suggesting that the microparticles contributed to the reduction of side effects such as increase in cholesterol, LDL, HDL and triglycerides plasmatic levels. It was observed decay in the quantification of pure drug during the period evaluated in the stability study. The microparticles showed no significant changes in the content of EFV during the 180 days. The thermograms showed no difference in the drug melting range and decays of thermogravimetric curves suggesting no formation of new products and consequently loss of stability. The evaluation of Carr index and Hausner factor indicated that M3 showed better flow and compression properties compared to pure EFV, characteristics which can improving the flow and to facilitate industrial routine.
Keywords: micropartículas; Eudragit; spray drying; cromatografia líquida de alta eficiência; perfil de liberação; parâmetros bioquímicos; propriedades de fluxo; microparticles; Eudragit; spray drying; high performance liquid chromatography; release profile; biochemical parameters; flow properties; CNPQ::CIENCIAS DA SAUDE::FARMACIA